BSCI-10. Invasive growth of brain metastases is driven by cancer cell-pSTAT3+ reactive astrocyte crosstalk. (9th August 2021) - Dankner, Matthew; Maritan, Sarah; Zhuang, Rebecca; Caron, Maxime; Priego, Neibla; Valiente, Manuel; Petrecca, Kevin; Siegel, Peter
Abstract: Background: Brain metastases (BrM) with a highly invasive (HI) histological growth pattern are associated with poor prognosis compared to minimally invasive (MI) masses. Compared to MI lesions, HI BrM form greater contacts with cells in the peritumoral brain, particularly reactive astrocytes (RAs). RAs expressing phosphorylated STAT3 (pSTAT3+RAs) have been shown to promote BrM colonization. Here, we investigate the role of pSTAT3+RAs in promoting invasive growth of HI BrM. Methods: We performed immunohistochemistry to identify pSTAT3+RAs in HI and MI human and patient-derived xenograft BrM. We assessed how pharmacological STAT3 inhibition or RA-specific STAT3 genetic ablation affected HI and MI BrM growth in vivo. scRNA-seq data generated from HI BrM astrocytes were integrated with published RA secretome data to identify STAT3 targets expressed by RAs that may drive invasion. Cancer cell invasion was modeled in vitro using a brain slice-tumor co-culture assay. Results: HI BrM display increased pSTAT3-positivity within RAs when compared to MI lesions. Pharmacological STAT3 inhibition with Legasil (Silibinin) or genetic ablation decreased in vivo growth of HI, but not MI, BrM. Brain slice cultures treated with STAT3-activating cytokines induced cancer cell invasion, a response that was ablated following STAT3 inhibition. Chi3L1 was identified as a STAT3 target expressed by RAs. Cancer cells treated with recombinant Chi3L1 showed greater invasion into brain slice cultures compared to untreated cells. Conclusions: pSTAT3+RAs are over-represented in HI BrM, rendering HI BrM preferentially sensitive to STAT3 inhibition. pSTAT3+RAs functionally contribute to BrM invasion within the brain, in part through Chi3L1-mediated activity. This work identifies STAT3 and Chi3L1 as clinically relevant therapeutic targets in management of HI BrM.